Complex production technology ball bearing steel ShH 15 SG at the "Belarussian Metallurgical Plant" RUP - V. I. Timoshpolsky; V. V. Filippov; A. B. Steblov; V. A. Tischenko; I. L. Numeranova; D. V. Lenartovich (Литьë и металлургия, 2001)
А technology of ball bearing steel at the "Belarussian Metallurgical Plant"RUP is worked out and possibility of its production is demonstrated. Technological parameters of smelting, pouring and rolling of steel are given.